2018
DOI: 10.1039/c8ew00686e
|View full text |Cite
|
Sign up to set email alerts
|

Organic and nitrogen load removal from bio-treated landfill leachates by a dual-anode system

Abstract: An efficient dual-anode system integrating anodic oxidation and electrocoagulation was developed for the removal of pollutants from bio-treated landfill leachate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…As noted in Table 6, most of the works dealt with low concentrations of ammonia (50-2240 mg/L) as compared to the current study with a much higher concentration of 3471 mg/L. Ammonia removal efficiencies of 14% to 37% were reported in most studies, except by [65] where 80 removal efficiency of ammonia was reported at longer electrolysis time (2 hours) by using dual-electrode anode and much lower ammonia concentration (50-110 mg/L). Whereas, this current research uses more economical operating parameters (Al anode) and less treatment duration (60 min).…”
Section: Comparison Of Treatment Performancementioning
confidence: 57%
“…As noted in Table 6, most of the works dealt with low concentrations of ammonia (50-2240 mg/L) as compared to the current study with a much higher concentration of 3471 mg/L. Ammonia removal efficiencies of 14% to 37% were reported in most studies, except by [65] where 80 removal efficiency of ammonia was reported at longer electrolysis time (2 hours) by using dual-electrode anode and much lower ammonia concentration (50-110 mg/L). Whereas, this current research uses more economical operating parameters (Al anode) and less treatment duration (60 min).…”
Section: Comparison Of Treatment Performancementioning
confidence: 57%